Ocular microbiota and lens contamination following Mel4 peptide-coated antimicrobial contact lens (MACL) extended wear. Issue 1 (February 2022) - Kalaiselvan, Parthasarathi; Dutta, Debarun; Bhombal, Faiza; Konda, Nagaraju; Vaddavalli, Pravin Krishna; Sharma, Savitri; Stapleton, Fiona; Willcox, Mark D.P.
Abstract: Purpose: The purpose of this study was to investigate the effect of Mel4 antimicrobial peptide-coated contact lenses (MACL) on the microbiota of the conjunctiva and lenses during three months of extended wear. Methods: One hundred and seventy-six participants were recruited into a randomised, contralateral, double masked, biweekly extended wear MACL and uncoated control lens trial. At the one month and 3-month visit, the conjunctival microbiota was sampled using sterile cotton swabs and contact lenses were collected aseptically. Standard microbiological procedures were employed for culture of the swabs and contact lenses and identification of the isolated microorganisms. Results: Gram-positive bacteria (predominantly coagulase-negative staphylococci) were the most frequently isolated microbes from both contact lenses and conjunctiva. There was no difference in the frequency of isolation of most bacteria or fungi from the conjunctival swabs of eyes wearing either MACL or control lenses. The only exception was a higher frequency of eyes harbouring Staphylococcus arlettae when wearing control lenses (5%) versus MACL (<1%) (p = 0.002). There was no significant difference in the frequency of microbes isolated from MACL or control contact lenses. There were also no differences between lens types in the frequency of isolation of >1 microbial type per sampling occasion for either conjunctiva swabs or contact lenses. Conclusion: MACL wear did not change the conjunctival microbiota during extended wear, and the types of microbes isolated from MACL were similar to those isolated from control lenses.